2018
DOI: 10.15403/jgld.2014.1121.274.cal
|View full text |Cite
|
Sign up to set email alerts
|

Fecal calprotectin correlates well with endoscopic activity in ulcerative colitis patients

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…Although fecal calprotectin is widely used in clinical practice to diagnose and monitor disease activity [ 23 , 24 ], more biomarkers are still needed to cover calprotectin´s limitations. Its sensitivity and specificity decrease in children and in patients with no inflammatory affectation of the large intestine [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although fecal calprotectin is widely used in clinical practice to diagnose and monitor disease activity [ 23 , 24 ], more biomarkers are still needed to cover calprotectin´s limitations. Its sensitivity and specificity decrease in children and in patients with no inflammatory affectation of the large intestine [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found several studies that solely focused on calprotectin and its predictive capabilities in assessing endoscopic disease activity in UC patients. Many publications demonstrated that fecal calprotectin levels correlated well with endoscopic activity in UC patients [ 29 , 30 ]. Similarly, the study conducted by D’Haens showed a strong association between calprotectin levels and endoscopic inflammation, suggesting its potential as a reliable biomarker [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…It serves as a marker of neutrophil migration within the GI tract and has a higher specificity than other inflammatory markers commonly used in clinical practice, such as C-reactive protein 21 . Levels of fecal calprotectin have been shown to correlate well with endoscopy and histopathologic metrics of disease activity and disease recurrence 22 , 23 . However, fecal calprotectin has several limitations.…”
Section: Discussionmentioning
confidence: 99%